2023
DOI: 10.56801/seejph.vi.309
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Big Data Quality Analytics on Knowledge Management in Healthcare Institutions: Lessons Learned from Big Data's Application within The Healthcare Sector

Abstract: It is widely acknowledged that knowledge management is critical to an organization's survival and growth. Every day, higher education institutions that are considered knowledge centers generate massive volumes of data. When this data is analyzed using appropriate computational methods and technology, it can provide knowledge to improve organizational performance and students' academic experience. Healthcare organizations create massive volumes of data as a result of the usage of digital technologies to manage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…The results of a study by (Maspul, 2021) showed that customers were satisfied with AI-based food production systems supporting sustainability in the United Arab Emirates by reducing carbon footprint, using fewer resources, and minimizing waste. Another study conducted by (Johnson et al, 2022) revealed that Apple and Google's privacy-centric changes impacted digital marketing strategies, targeting, measurement, and emphasizing privacy in digital advertising (Ravikumar et al, 2023;Salameh et al, 2022;Shwedeh, Adelaja, et al, 2023). (Vinuesa et al 2020) used the term "Sustainable AI" to refer to artificial intelligence that contributes to achieving Sustainable Development Goals (SDGs).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The results of a study by (Maspul, 2021) showed that customers were satisfied with AI-based food production systems supporting sustainability in the United Arab Emirates by reducing carbon footprint, using fewer resources, and minimizing waste. Another study conducted by (Johnson et al, 2022) revealed that Apple and Google's privacy-centric changes impacted digital marketing strategies, targeting, measurement, and emphasizing privacy in digital advertising (Ravikumar et al, 2023;Salameh et al, 2022;Shwedeh, Adelaja, et al, 2023). (Vinuesa et al 2020) used the term "Sustainable AI" to refer to artificial intelligence that contributes to achieving Sustainable Development Goals (SDGs).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%